A phase II trial of durvalumab and tremelimumab in metastatic, non‐urothelial carcinoma of the urinary tract. (31st December 2020) - Sarfaty, Michal; Whiting, Karissa; Teo, Min Yuen; Lee, Chung‐Han; Peters, Vanessa; Durocher, Jennifer; Regazzi, Ashley M.; McCoy, Asia S.; Hettich, Grace; Jungbluth, Achim A.; Al‐Ahmadie, Hikmat; Ostrovnaya, Irina; et al.
Abstract: Background: Immune checkpoint blockade has made a significant impact on the clinical outcomes of patients with metastatic urothelial carcinoma (UC). However, evidence for this approach in patients with non‐UC of the urinary tract is limited. Methods: This was a phase II open‐label study of durvalumab 1500 mg and tremelimumab 75 mg every 4 weeks for four cycles followed by durvalumab 1500 mg every 4 weeks. Eligible patients had metastatic non‐UC with ECOG PS 0–1 regardless of prior therapy (except small cell carcinoma who were pretreated). The primary endpoint was overall response rate per RECIST v1.1. A Simon's minimax two‐stage design was employed, with 13 patients planned for stage one. Pre‐treatment tumors underwent PD‐L1 staining and next‐generation sequencing. Results: Thirteen patients were treated, including seven small cell carcinoma, three squamous cell carcinoma, and three adenocarcinoma. Eleven patients had visceral metastases. No responses were observed; 11 patients had PD and 2 patients had SD. Median PFS was 1.8 months (95% CI, 1.25‐not reached [NR]) with a median follow‐up of 7.38 months (range, 5.23–21.99 months). Median OS was 6.97 months (95% CI, 4.34‐NR). One patient's tumor was PD‐L1 positive and all sequenced tumors ( n  = 8) were microsatellite stable. Grades 3–4 treatment‐related adverse events occurred in 38.4% of patients. Conclusions: In a poor prognosis cohort of patients with non‐UC, durvalumab and tremelimumab lacked clinical activity while demonstrating a manageable safety profile. Abstract : Metastatic, non‐UC tumors of the urinary tract have an aggressive clinical course and dismal prognosis. This phase II trial evaluating durvalumab and tremelimumab demonstrated a manageable safety profile but lack of clinical activity.